Nivolumab induced encephalopathy in a man with metastatic renal cell cancer: a case report - Kopecký, Jindřich; Kubeček, Ondřej; Geryk, Tomáš; Slováčková, Birgita; Hoffmann, Petr; Žiaran, Miroslav; Priester, Peter (Journal of medical case reports, 2018)
BACKGROUND: Great progress has recently been made in the treatment of metastatic renal cell carcinoma, including the introduction of nivolumab, an immune checkpoint inhibitor. Despite promising results, this treatment brings a completely new spectrum of adverse events, distinct from those experienced with small-molecule kinase inhibitors. Neurologic immune-related adverse events may be serious and potentially life-threatening complications requiring immediate immunosuppressive therapy. Only a few cases of immune-related encephalitis induced by checkpoint inhibitors have been described and the data regarding the management of this serious adverse event are limited. CASE PRESENTATION: We report the case of a 63-year-old white man with metastatic renal cancer who developed severe chorea-like dyskinesia during nivolumab therapy. The findings on brain magnetic resonance imaging and flow cytometry of cerebrospinal fluid, and the positivity of anti-paraneoplastic antigen Ma2 immunoglobuline G class autoantibodies were consistent with a diagnosis of immune-related encephalitis. High-dose intravenous corticosteroid therapy was started immediately, with no signs of improvement, even when infliximab was added. Our patient refused further hospitalization and was discharged. Three weeks later, he presented with signs of severe urosepsis. Despite intensive treatment, he died 4 days after admission. CONCLUSIONS: The management of less frequent immune-related adverse events has not been fully established and more information is required to provide uniform recommendations. Immune-related encephalitis is a severe and potentially fatal complication requiring immediate hospital admission and extensive immunosuppressive therapy. The examination of cerebrospinal fluid for paraneoplastic antibodies, such as anti-N-methyl-D-aspartate receptor and anti-Ma2 antibodies, in order to distinguish autoimmune etiology from other possible causes is essential and highly recommended.
Keywords: Male; Nivolumab; Middle Aged; protinádorové látky imunologicky aktivní; nivolumab; Carcinoma, Renal Cell; mužské pohlaví; Kidney Neoplasms; encefalitida; Case report; karcinom z renálních buněk; lidé středního věku; Renal cancer; Immune-related adverse event; nádory ledvin; Encephalitis; lidé; Humans; Antineoplastic Agents, Immunological